De re aedificatoria column systematization shape grammar - Quaresma, Pedro Filipe Coutinho (2014)
An underlying inﬂuence of Alberti’s theory is felt in classical architecture in Portugal, but no one was able to determine the extent of such an inﬂuence. The idea is to contribute for further methodology and data by translating the treatise into a description grammar (Stiny, 1981) and a shape grammar (Stiny and Gips, 1972) and tracing the inﬂuence of Alberti’s work by determining to which extent this grammar can account for the generation of some Portuguese classical buildings. This approach follows the transformations in design framework proposed by Knight, (1983) according to which the transformation of one style into another can be explained by changes of the grammar underlying the frst style into the grammar of the second. The income paper will show the developed grammar that leads us to some implementation as computer programs (Python and Grasshopper). The output digital models (2D and 3D) will be used to produce drawings and rapid prototyping models.